2020
DOI: 10.31690/ijnr.2020.v06i02.003
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Knowledge and Perception among Budding Nurses: A Questionnaire-Based Survey

Abstract: Background and Aim: In COVID-19 pandemic, a global emergency, there is a scarcity of resources including workforce in health-care system. Budding nurses as additional workforce are being utilized in COVID-19 units, where their knowledge and perception about COVID-19 plays a key role in patient care as well as for their safety. There is a paucity of regional data on knowledge and perception of budding nurses about COVID-19. The present study was conducted with an aim to assess the knowledge and perception of bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…11 Similarly, a survey done in India during April 2020 (n=380), found that most (89.74%) of budding nurses responded that fever, fatigue, dry cough, and headache are the main clinical manifestations of COVID-19. 12 Likewise, 114(91.9%) B.Sc. nursing students of Saudi Arabia knew about the main symptoms of COVID- 19.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similarly, a survey done in India during April 2020 (n=380), found that most (89.74%) of budding nurses responded that fever, fatigue, dry cough, and headache are the main clinical manifestations of COVID-19. 12 Likewise, 114(91.9%) B.Sc. nursing students of Saudi Arabia knew about the main symptoms of COVID- 19.…”
Section: Resultsmentioning
confidence: 99%
“…A study done in India revealed similar results, in which 260(68.42%) budding nurses strongly agreed on wearing general medical masks by people to prevent the spread of coronavirus infection caused by COVID-19, and 365(96.05%) replied that people should avoid going to crowded places such as train stations and avoid taking public transportation to prevent the infection. 12 However, in Pakistan, 64.7% of health care workers obtained an overall moderate-to-poor score regarding the correct usage of a surgical face mask to limit the spread of COVID-19. 16 In this study, knowledge of the correct duration of quarantine for suspected cases was known by 351(91.9%).…”
Section: Resultsmentioning
confidence: 99%
“…The covid-19 vaccine was extremely fruitful against covid-19 [11]. some experts declare that the vaccine protected against covid-19 in 62% of those who received two full doses and 90% of those who initially received half dose [12,13,15]. OBJECTIVE: 1.…”
Section: Resultsmentioning
confidence: 99%
“…All these facilities and services are available in the private hospitals. 30 A negative relationship between knowledge and attitude (r = -.178, p = .000). It means that knowledge is increased but attitude remain unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The current study results regarding item analysis were quite similar with the previous study of Egypt, India, and Nepal. [30][31][32] The findings might be due to as anew emerging disease, sign and symptoms, mode of transmission, prevention and management of this fatal disease has not yet been identified. Treatment guidelines or nursing management has not been developed.…”
Section: Discussionmentioning
confidence: 99%